B Cell-Based Vaccine Transduced With ESAT6-Expressing Vaccinia Virus and Presenting α-Galactosylceramide Is a Novel Vaccine Candidate Against ESAT6-Expressing Mycobacterial Diseases - Kwon, Bo-Eun; Ahn, Jae-Hee; Park, Eun-Kyoung; Jeong, Hyunjin; Lee, Hyo-Ji; Jung, Yu-Jin; Shin, Sung Jae; Jeong, Hye-Sook; Yoo, Jung Sik; Shin, EunKyoung; Yeo, Sang-Gu; Chang, Sun-Young; et al. (Frontiers in Immunology, 2019)
Early secretory antigenic target-6 (ESAT6) is a potent immunogenic antigen expressed in Mycobacterium tuberculosis as well as in some non-tuberculous mycobacteria (NTM), such as M. kansasii. M. kansasii is one of the most clinically relevant species of NTM that causes mycobacterial lung disease, which is clinically indistinguishable from tuberculosis. In the current study, we designed a novel cell-based vaccine using B cells that were transduced with vaccinia virus expressing ESAT6 (vacESAT6), and presenting -galactosylceramide (αGC), a ligand of invariant NKT cells. We found that B cells loaded with αGC had increased levels of CD80 and CD86 after in vitro stimulation with NKT cells. Immunization of mice with B/αGC/vacESAT6 induced CD4+ T cells producing TNF-α and IFN-γ in response to heat-killed M. tuberculosis. Immunization of mice with B/αGC/vacESAT6 ameliorated severe lung inflammation caused by M. kansasii infection. We also confirmed that immunization with B/αGC/vacESAT6 reduced M. kansasii bacterial burden in the lungs. In addition, therapeutic administration of B/αGC/vacESAT6 increased IFN-γ+ CD4+ T cells and inhibited the progression of lung pathology caused by M. kansasii infection. Thus, B/αGC/vacESAT6 could be a potent vaccine candidate for the prevention and treatment of ESAT6-expressing mycobacterial infection caused by M. kansasii.